Comparison of cardiorespiratory fitness levels between wearing and not wearing masks in physiotherapy students - Ni Made Wulan Handayani Adiniti Adiniti; Ni Komang Ayu Juni Antari; Ni Wayan Tianing; Made Hendra Satria Nugraha (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Masks, devices used to cover the face, nose, and mouth area to prevent the transmission of viruses, bacteria, diseases, and air pollution, have become a topic of pros and cons among the public regarding their impact on cardiorespiratory fitness during physical activity, as some claim that masks decrease airflow to the lungs thus reducing oxygen in the blood and muscles which makes activity more difficult, while other studies have shown no difference in cardiorespiratory fitness values with or without masks. The purpose of this study was to determine the difference in cardiorespiratory fitness levels when wearing a mask and not wearing a mask in physiotherapy students. Methods: This study used an analytical observational design with a one-group pre-post test design and a consecutive sampling technique involving 35 physiotherapy students from the Faculty of Medicine, Universitas Udayana. This research was conducted at the Physiotherapy Building, Faculty of Medicine, Universitas Udayana, in June 2023. The inclusion criteria included physiotherapy students aged ≥ 18 with normal vital signs who used a 3-ply surgical mask. The exclusion criteria were students with a history of respiratory problems and those who did not use a 3-ply surgical mask. Cardiorespiratory fitness was measured using the Harvard step test. Results: This study showed that the research subjects were dominated by students with poor cardiorespiratory fitness when wearing a mask or not wearing a mask, namely 35 students (100%). Conclusion: There was no significant difference in cardiorespiratory fitness levels between mask wearers and non-wearers, with a p-value of 0.180 (>0.05).